Volatile organic compounds in human matrices as lung cancer biomarkers: a systematic review. (September 2020) - Janssens, Eline; van Meerbeeck, Jan P; Lamote, Kevin
Highlights: Volatile organic compounds are promising biomarkers for lung cancer diagnosis. Different human matrices can be explored as sources of volatile biomarkers. Lack of standardisation limits study quality and comparability. In vitro research can uncover metabolic pathways and biomarker distribution. Validation of relevant identified biomarkers by prospective trials is needed. Abstract: Volatile organic compounds (VOCs) have shown potential as non-invasive breath biomarkers for lung cancer, but their unclear biological origin currently limits clinical applications. This systematic review explores headspace analysis of VOCs in patient-derived body fluids and lung cancer cell lines to pinpoint lung cancer-specific VOCs and uncover their biological origin. A search was performed in the databases MEDLINE and Web of Science. Twenty-two articles were included in this systematic review. Since there is no standardised approach to analyse VOCs, a plethora of techniques and matrices/cell lines were explored, which is reflected in the various VOCs identified. However, comparing VOCs in the headspace of urine, blood and pleural effusions from patients and lung cancer cell lines showed some overlapping VOCs, indicating their potential use in lung cancer diagnosis. This review demonstrates that VOCs are promising biomarkers for lung cancer. However, due to lack of inter-matrix consensus, standardised prospective trials will have to be conducted to validate clinically relevant biomarkers.